POPULAR CULTURE OF MAIN CHARACTER IN CONFESSIONS OF A SHOPAHOLIC MOVIE DIRECTED BY P. J. HOGAN - Chodidjah Chodidjah; Dadan Hidayat; Luspianti Pratiwi (Politeknik Negeri Bengkalis, 2021)
The objective of this paper is to know about popular culture especially type of popular culture which occurred in today society and the moral value. This analysis is done based on the source of movie is Confessions of a Shopaholic which focuses on main character only. The writer uses descriptive qualitative method for this analysis which focused on Brummet’s theory of popular culture as the main subject. The result indicates that there are two types of popular culture based on Brummet’s category, there are top down and bottom up. First is top down, which consist of eight points: branded-product, fancy store, shopaholic, credit card, look, property, taxi, and gadget. Second is bottom up, which consists of two points, there are: boot and coat. The writer considered that the most dominant type from those two types and ten points is top down. While for the moral values from the movie, the writes takes six points there are: confront the expenditure, do not let things define you, cost and worth are very different things, credit cards are not magic wands, lying is not a good idea, and everything happens for a reason. Keyword: Main Character, Movie, Popular Culture.